Vital Texts and Bare Life: The Uses and Abuses of Life in Contemporary Fiction. Issue 2 (August 2015) - Noys, Benjamin
<x content-type="archive" xml:space="preserve">Abstract</x> The problem of writing life is one that has not dissipated in contemporary literature, if anything it has intensified. Past forms of countertexts turned to the subversive power of life, either with the avant-garde dissolution of text into life or by the modernist merging of life into the text. These forms often deployed a literary vitalism, which claimed a countertextual force through staking a claim on the power of life to overflow textual and political determinations. These currents, however, risk reinforcing forms of literary and capitalist value that draw on the powers of life. Instead, I argue, a different form of countertextuality can be found in contemporary autobiographical or confessional works, which by foregrounding the life of the author render the smooth translation of life into the text problematic. In particular, the work of the contemporary US writer Chris Kraus probes the relation between 'vital texts' and the experience of 'bare life' – life left exposed to power. Reconstructing her intervention, especially in her novel Summer of Hate (2012), reveals the possibilities of a new countertextual sensibility that turns to subjectivity and life without simply celebrating the expressive powers of life as the ground of literary and cultural value. Instead of a countertext that claims to express the power of life beyond the literary, Kraus develops a countertext in which life is exposed to abstract forms of power and so she allows us to trace the entanglement of life with value.